2000
DOI: 10.1002/1529-0131(200008)43:8<1831::aid-anr19>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of anti-cyclic citrullinated peptide antibody in patients with recent-onset rheumatoid arthritis

Abstract: Our data show that in almost 70% of RA patients, anti-CCP antibody is present at the early stages of disease. Anti-CCP-positive patients developed significantly more severe radiologic damage than patients who were anti-CCP negative, although in multiple regression analysis the additional predictive value was rather moderate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
285
4
26

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 546 publications
(344 citation statements)
references
References 15 publications
23
285
4
26
Order By: Relevance
“…However, the actual classification impact achieved using AKA compared with using rheumatoid factor as the sole laboratory criterion was very modest, mainly because the criteria were strongly interrelated. A similar study by Kroot and colleagues (20) using an anti-CCP ELISA found that almost 70% of RA patients were positive for anti-CCP in early RA and they had more radiologic damage. However, multiple regression analyses demonstrated that the additional predictive value given by anti-CCP ELISAs was only moderate (20).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…However, the actual classification impact achieved using AKA compared with using rheumatoid factor as the sole laboratory criterion was very modest, mainly because the criteria were strongly interrelated. A similar study by Kroot and colleagues (20) using an anti-CCP ELISA found that almost 70% of RA patients were positive for anti-CCP in early RA and they had more radiologic damage. However, multiple regression analyses demonstrated that the additional predictive value given by anti-CCP ELISAs was only moderate (20).…”
mentioning
confidence: 70%
“…A similar study by Kroot and colleagues (20) using an anti-CCP ELISA found that almost 70% of RA patients were positive for anti-CCP in early RA and they had more radiologic damage. However, multiple regression analyses demonstrated that the additional predictive value given by anti-CCP ELISAs was only moderate (20). Another report, by Van Jaarsveld et al (21), evaluated the clinical value of the anti-CCP ELISA in combination with rheumatoid factor status in 249 patients with early RA.…”
mentioning
confidence: 70%
“…Their cause and role remain unclear despite intense research [3]. Antibodies towards epitopes on arginine-rich proteins modified through citrullination occur frequently in RA and are today becoming one of the best diagnostic factors [4,5], although their cause and role are again still unclear [6,7]. Autoantibodies towards joint components, like type II collagen (CII) are also known to occur, but only in a minority of RA cases [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Kuhn et al, for example, recently demonstrated that administration of anti-citrullinated fibrinogen antibodies enhanced disease severity in an experimental mouse model of arthritis (4). In the majority of patients with RA, the presence of ACPAs antedates disease onset (5,6), and ACPA-positive patients present with a more severe and erosive form of arthritis (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). A commercial enzyme-linked immunosorbent assay (ELISA) based on cyclic citrullinated peptides (CCPs) detects ACPAs and is now routinely used in the diagnosis of RA.…”
mentioning
confidence: 99%